Contributions to the understanding of the mechanisms underlying the susceptibility and resistance of common bean to Xanthomonas citri pv. fuscans - Silva, Nikolas Emanuel Chaves (2023)
Common Bacterial Blight (CBB) is a disease of common bean (Phaseolus vulgaris L.) caused by Xanthomonas citri pv. fuscans (Xcf) and X. phaseoli pv. phaseoli with significant importance worldwide. The most recommended control method for the disease is the use of resistant cultivars. Several studies have shown that the resistance of common bean to CBB is primarily non-race-specific, quantitative and oligogenic. In previous studies conducted by the Laboratory of Molecular Phytobacteriology at the Universidade Federal de Vicosa, varieties resistant and susceptible to CBB were identified among a set of Brazilian varieties, but the mechanisms subjacent to these reactions during the common bean-Xanthomonas interactions are not fully understood. It is known that during the early stages of plant-bacteria interactions, plant hormones such as salicylic acid, jasmonic acid, and ethylene, accumulate in plant tissue concomitant with activation of other responses associated with the oxidative stress and key defense enzymes, such as phenylalanine ammonia-lyase. In order to subvert the plant defense response and to acquire nutrients, some phytopathogenic Xanthomonas species produce Transcriptional Activator-Like Effector (TALE) proteins, which are injected into the plant cell cytoplasm through a type III secretion system. Then, these TALE proteins reach the plant nucleus where they activate the expression of susceptibility genes. Identifying the repertoire of TALE proteins produced by Xanthomonas and their putative host target genes can provide important insights into the mechanisms that determine plant susceptibility. This Master’s degree dissertation aimed to predict the TALE repertoire in a set of 39 Xcf strains and their P. vulgaris gene targets using genome sequences publicly available in GenBank (Chapter 1), and to assess differences in the activity of enzymes involved in plant defense and oxidative stress between P. vulgaris genotypes resistant (BC3F4 derived from a BRS Radiante × Carioca MG cross) and susceptible (Carioca MG) to Xcf (Chapter 2). A total of 56 different TALE genes were identified in the investigated Xcf strains, which were predicted to have six conserved binding sites in the P. vulgaris genome. Overall, higher defense-related enzyme activities were observed in the resistant genotype compared to the susceptible one at 48 h post-inoculation with Xcf, which was consistent with a significant difference in bacterial population sizes in leaf tissue between the genotypes. These results provide important insights into the molecular mechanisms underlying the susceptibility and biochemical mechanisms subjacent to the resistance of P. vulgaris to Xcf. Keywords: Common Bacterial Blight. Plant-defense enzymes. Phaseolus vulgaris. TALE.